Solvent Effects of the Electronic Absorption Spectrum of Ferroin Molecule - Kumar, A.; Shrivastava, K.P. (Asian Journal of Chemistry, 2010)
In order to explore the role of the solvents on one of the best indicators, 1: 10-phenanthroline ferrous sulphate, i.e., ferroin, through ultraviolet spectroscopy, λmax, εmax and oscillator strength have been determined at room temperature. The present results together with values obtained from the experiments in water, methanol, acetone and orthophosphoric acid have been discussed in terms of ion-solvent interactions and solvent polarity. The intense long wavelength band which appears at about 510 nm in the visible region is referred to as the 1A → 1A1 or V ← N band. It is expected that the interaction affects the symmetry of the bidentate ligand with Fe2+ ion in the molecule to some extent depending on its nature.